Beyond higher yields: the impact of sweetpotato integrated crop management and farmer field schools in Indonesia - Fliert, E. van de; Johnson, N.; Asmunati, R.; Wiyanto (1999)
A pilot program of sweetpotato (/pomoea batatas (L.) Lam) integrated crop management (ICM)-farmer field schools (FFSs) was implemented in six communities in Indonesia, using protocols developed jointly by a team of farmers, researchers, and development workers. Monitoring and evaluation studies showed that participation in the FFS enhanced farmers' crop management knowledge and skills. Several of their changed cultivation practices led to increased net income as a result of reduced cultivation costs and/or increased yields. Farmer participation in research was shown to have contributed to the relevancy, appropriateness, and impact of the sweetpotato ICM-FFS protocols.